Analisis Problematika Kerja Malam bagi Karyawan Wanita di Centerstage Hotel XYZ - I Wayan Eka Sudarmawan (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2021)
Background: Female workers have many job opportunities in tourism and hospitality service companies. The company enforces working hours until the evening for both female and male employees. This is a separate problem for female employees in terms of security and health. Objective: to find out the problems of night work for female employees at Hotel XYZ. Design: qualitative descriptive research design with primary data sources through interviews with 6 (six) female employees who work at Hotel XYZ. Results: (1) work shifts: Hotel has implemented government regulations by not hiring female employees under 18 years old, and not providing night shifts for pregnant women employees, (2) transportation problems: Hotel has not implemented government regulations, namely , has not prepared special transportation for female employees who come home at night, (3) security issues: Hotel has provided nutritious, clean, and varied food, and has prepared security to maintain the safety and decency of female employees who work at night, (4) maternity leave: Hotel has implemented government regulations, namely providing three months of leave to female employees who are pregnant, (5) breastfeeding opportunities: Hotel has not implemented government regulations, namely, has not prepared a special room for expressing breast milk (lactation room).